Advances in Regenerative Endodontics: Pulp Revitalization and Future Directions - Wadhwa, Rohit (International Journal of Health and Clinical Research, 2022)
Regenerative endodontics has become an innovative form of treatment in the field of dentistry forcing a paradigm shift in dental practice to current root canal treatment to one that views the endodontic field as biologically driven pulp regeneration. The profession focuses on the regenerative treatment of the pulp-dentin unit using the stem cell, regenerative scaffold, and growth factors to restore the vitality of the tooth and extend its functional life. The innovations in the field of imaging technologies, like cone-beam computed tomography, have improved the accuracy of the diagnostics and regenerative outcome monitoring. Moreover, the inclusion of AI in endodontics practice will provide the chance of precise selection of cases, treatment planning, and prognostication of outcomes. There is clinical evidence that regenerative protocols can play not only a structural reinforcement role in teeth treated endodontically or have positive indications in both immature and mature permanent dentition. Even though much has been done, there are still setbacks regarding standardization of treatment mechanisms, the promise of definite results and barriers to translation. Future perspectives hold the promise of integration between biomaterial science, nanotechnology and artificial intelligence-based predictive modeling in optimizing pulp revitalization and making regenerative endodontics a full-fledged modality.